An HPLC-based Assay to Study the Activity of Cyclic Diadenosine Monophosphate (C-di-AMP) Synthase DisA from Mycobacterium smegmatis - Avisek Mahapa; Sudhanshu Gautam; Arti Rathore; Dipankar Chatterji (Bio-Protocol)
Cyclic diadenosine monophosphate (c-di-AMP) is a recently discovered second messenger that modulates several signal transduction pathways in bacterial and host cells. Besides the bacterial system, c-di-AMP signaling is also connected with the host cytoplasmic surveillance pathways (CSP) that induce type-I IFN responses through STING-mediated pathways. Additionally, c-di-AMP demonstrates potent adjuvant properties, particularly when administered alongside the Bacillus Calmette–Guérin (BCG) vaccine through mucosal routes. Because of its pivotal role in bacterial signaling and host immune response, this molecule has garnered significant interest from the pharmaceutical industry. This protocol outlines the quantification of c-di-AMP by an HPLC-based assay to enumerate the activity of c-di-AMP synthase from Mycobacterium smegmatis. The following protocol is designed to be generic, enabling the study of c-di-AMP synthase activity from other bacterial species. However, modifications may be required depending on the specific activity of c-di-AMP synthase from different bacterial sources.